2023
DOI: 10.1002/pbc.30336
|View full text |Cite|
|
Sign up to set email alerts
|

Cerebral revascularization surgery reduces cerebrovascular events in children with sickle cell disease and moyamoya syndrome: Results of the stroke in sickle cell revascularization surgery retrospective study

Abstract: Background Recent studies suggest that cerebral revascularization surgery may be a safe and effective therapy to reduce stroke risk in patients with sickle cell disease and moyamoya syndrome (SCD–MMS). Methods We performed a multicenter, retrospective study of children with SCD–MMS treated with conservative management alone (conservative group)—chronic blood transfusion and/or hydroxyurea—versus conservative management plus surgical revascularization (surgery group). We monitored cerebrovascular event (CVE) ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Protective effect of aspirin against CVE may be another confounding variable" Contrary to the protective effect against CVE as stated, our study found that patients on antiplatelet therapy had significantly increased odds of CVE occurrence (OR = 7.45, p < .001; Table S1). 2 Despite the Surgery group having significantly more patients on antiplatelet therapy, which appeared to increase CVEs, they still had a lower odds of CVE occurrence.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Protective effect of aspirin against CVE may be another confounding variable" Contrary to the protective effect against CVE as stated, our study found that patients on antiplatelet therapy had significantly increased odds of CVE occurrence (OR = 7.45, p < .001; Table S1). 2 Despite the Surgery group having significantly more patients on antiplatelet therapy, which appeared to increase CVEs, they still had a lower odds of CVE occurrence.…”
mentioning
confidence: 98%
“…
We read with interest the Highlight article by Dr. Hsu that reviewed our Stroke in Sickle Cell Revascularization Surgery (SiSCRS) study published in the same issue of Pediatric Blood & Cancer. 1,2 We agree that further research is needed to determine which children with sickle cell disease and moyamoya syndrome (SCD-MMS) would benefit from cerebral revascularization surgery (CRS).We want to highlight several inaccuracies and weaknesses in the arguments used in the critique.
…”
mentioning
confidence: 99%